Global monetary policy shocks in the G5: A SVAR approach - Joao Miguel Sousa; Andrea Zaghini (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
The paper constructs a global monetary aggregate, namely the sum of the key monetary aggregates of the G5 economies (US, Euro area, Japan, UK, and Canada), and analyses its indicator properties for global output and inflation. Using a structural VAR approach we find that after a monetary policy shock output declines temporarily, with the downward effect reaching a peak within the second year, and the global monetary aggregate drops significantly. In addition, the price level rises permanently in response to a positive shock to the global liquidity aggregate. The similarity of our results with those found in country studies might supports the use of a global monetary aggregate as a summary measure of worldwide monetary trends.
urn:nbn:de:hebis:30-38048
Keywords: E52; F01; 330; Monetary Policy; Structural VAR; Global Economy; Geldpolitik; Schock; VAR-Modell; Weltmodell; G-5-Staaten